THE CORRELATION BETWEEN SOURCE OF AWARENESS TO BRAND AWARENESS WITH BUYING DECISION IN WEST JAVA FMCG CONSUMER - Rachmansyah, Arief (Journal of Business and Management Inaba, 2022)
Social media is a source of awareness among many other sources of awareness such as TV/radio, billboards/outdoor media, outlets such as shops, mini markets, stalls, people around such as friends, family etc. This study aims to find out how often people use, seek information and see advertisements on social media, and does this affect the effectiveness of social media sources of awareness? Also to find out whether brand awareness affects purchasing decisions? Especially for brand awareness in the food and beverage product category. Data were collected from 531 respondents using the survey method through a structured questionnaire with a seven-point Likert scale. Data analysis used frequency analysis, mean, standard deviation and regression analysis. In this study it was found that the frequency of people using social media is very high and social media is an effective source of awareness which ultimately has a significant effect on purchasing decisions.